Diagnostic Determinants of Proliferative Lupus Nephritis Based on Clinical and Laboratory Parameters: A Diagnostic Study - Aida Lydia; Mita Hafsah Saraswati; Dharmeizar Dharmeizar; Meilania Saraswati; Siti Setiati (Acta Medica Indonesiana)
Background: proliferative lupus nephritis (LN) has higher prevalence and worse prognosis than non-proliferative LN. Renal biopsy plays an important role in diagnosis and therapy of LN, but there are some obstacles in its implementation. A diagnostic scoring system for proliferative LN is necessary, especially for cases in which renal biopsy cannot be performed. This study aimed to develop a diagnostic scoring system of proliferative LN based on its diagnostic determinants including hypertension, proteinuria, hematuria, eGFR, anti-dsDNA antibody, and C3 levels. Methods: a cross-sectional study with total sampling method was conducted. Our subjects were adult LN patients who underwent renal biopsy in Cipto Mangunkusumo Hospital between January 2007 and June 2017. Results: from a total of 191 subjects with biopsy-proven LN in this study, we found a proportion of proliferative LN of 74.8%. There were 113 subjects included for analysis of proliferative LN determinants. The multivariate analysis demonstrated that determinants for proliferative LN were hypertension (OR 3.39; 95% CI 1.30-8.84), eGFR <60ml/min/1.73m2 (OR 9.095; 95% CI 1.11-74.68), and low C3 levels (OR 3.97; 95% CI 1.41-11.17). After further analysis, we found that hypertension, eGFR <60ml/min/1.73m2, low C3 levels, and hematuria were essential components of the diagnostic scoring system on proliferative LN. The scoring system was tested with ROC curve and an AUC of 80.4% was obtained (95% CI 71.9-89). Conclusion: the proportion of proliferative LN in biopsy-proven LN patients of Cipto Mangunkusumo Hospital is 74.8%. Components of scoring system for proliferative LN consist of hypertension, eGFR <60ml/min/1.73m2, low C3 levels, and hematuria.